2015
DOI: 10.1002/bit.25847
|View full text |Cite
|
Sign up to set email alerts
|

On‐chip assessment of human primary cardiac fibroblasts proliferative responses to uniaxial cyclic mechanical strain

Abstract: Cardiac cell function is substantially influenced by the nature and intensity of the mechanical loads the cells experience. Cardiac fibroblasts (CFs) are primarily involved in myocardial tissue remodeling: at the onset of specific pathological conditions, CFs activate, proliferate, differentiate, and critically alter the amount of myocardial extra-cellular matrix with important consequences for myocardial functioning. While cyclic mechanical strain has been shown to increase matrix synthesis of CFs in vitro, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 68 publications
4
40
0
Order By: Relevance
“…Mechanical strain significantly impacted cell proliferation within the PX culture condition: culturing CFs at PX and subjecting them to 2% strain induced a striking increase in mitotic cells compared to no strain control and 8% strain cultures. This strain intensity-dependent effect is in line with our previous investigations of CF proliferation under mechanical strain in NX conditions (Ugolini et al, 2016). After 12 hr of stimulation, the proliferative increase with HX is not statistically significant, while we report a significant synergistic decrease of mitotic cells induced by the combination of 8% strain and HX (Figure 2—figure supplement 1).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Mechanical strain significantly impacted cell proliferation within the PX culture condition: culturing CFs at PX and subjecting them to 2% strain induced a striking increase in mitotic cells compared to no strain control and 8% strain cultures. This strain intensity-dependent effect is in line with our previous investigations of CF proliferation under mechanical strain in NX conditions (Ugolini et al, 2016). After 12 hr of stimulation, the proliferative increase with HX is not statistically significant, while we report a significant synergistic decrease of mitotic cells induced by the combination of 8% strain and HX (Figure 2—figure supplement 1).…”
Section: Resultssupporting
confidence: 92%
“…To explore these effects we employed low cyclic strain mimicking reduced contractility (2% strain), physiological cyclic strain (8% strain) and a static control. These values were based on cardiac imaging studies performed shortly after myocardial injury (Dandel et al, 2009; Vartdal et al, 2007) and were previously reported to elicit strain-dependent effects in CFs (Ugolini et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations